Self-monitoring of oral anticoagulation: systematic review and meta-analysis of individual patient data. - Heneghan, C; Ward, A; Perera, R; Bankhead, C; Fuller, A; Stevens, R; Bradford, K; Tyndel, S; Alonso-Coello, P; Ansell, J; Beyth, R; Bernardo, A; et al. (2012)
BACKGROUND: Uptake of self-testing and self-management of oral anticoagulation [corrected] has remained inconsistent, despite good evidence of their effectiveness. To clarify the value of self-monitoring of oral anticoagulation, we did a meta-analysis of individual patient data addressing several important gaps in the evidence, including an estimate of the effect on time to death, first major haemorrhage, and thromboembolism. METHODS: We searched Ovid versions of Embase (1980-2009) and Medline (1966-2009), limiting searches to randomised trials with a maximally sensitive strategy. We approached all authors of included trials and requested individual patient data: primary outcomes were time to death, first major haemorrhage, and first thromboembolic event. We did prespecified subgroup analyses according to age, type of control-group care (anticoagulation-clinic care vs primary care), self-testing alone versus self-management, and sex. We analysed patients with mechanical heart valves or atrial fibrillation separately. We used a random-effect model method to calculate pooled hazard ratios and did tests for interaction and heterogeneity, and calculated a time-specific number needed to treat. FINDINGS: Of 1357 abstracts, we included 11 trials with data for 6417 participants and 12,800 person-years of follow-up. We reported a significant reduction in thromboembolic events in the self-monitoring group (hazard ratio 0·51; 95% CI 0·31-0·85) but not for major haemorrhagic events (0·88, 0·74-1·06) or death (0·82, 0·62-1·09). Participants younger than 55 years showed a striking reduction in thrombotic events (hazard ratio 0·33, 95% CI 0·17-0·66), as did participants with mechanical heart valve (0·52, 0·35-0·77). Analysis of major outcomes in the very elderly (age ≥85 years, n=99) showed no significant adverse effects of the intervention for all outcomes. INTERPRETATION: Our analysis showed that self-monitoring and self-management of oral coagulation is a safe option for suitable patients of all ages. Patients should also be offered the option to self-manage their disease with suitable health-care support as back-up. FUNDING: UK National Institute for Health Research (NIHR) Technology Assessment Programme, UK NIHR National School for Primary Care Research.